Electrochemical Model Parameter Estimation of a Lithium-Ion Battery Using a Metaheuristic Algorithm : Cascaded Improved Harmony Search. Issue 28 (2018) - Chun, Huiyong; Han, Soohee
Abstract: For the safe and accurate operation of lithium-ion battery, the estimation of inner states of battery is necessary. Among many models of battery, electrochemical model, especially P2D model, represents the real dynamics such as transport and diffusion phenomena of charges and lithium-ions. For this reason, P2D model is an appropriate model for estimating the states. In this paper, metaheuristic algorithm is applied to estimate these parameter values, since it is more useful to implement the metaheuristic method than other jacobian-based methods, if the number of the parameters to be estimated is increased. Harmony search is one of the metaheuristic algorithms, and improved harmony search was developed for high convergence rate and fine-tunning. The cascaded version of improved harmony search is proposed as the estimation algorithm in this paper, and it is the first time to using the harmony search for lithium-ion battery parameterization. As a result, the parameters had reasonable values compared to reference values and lower voltage, temperature errors compared to the results of improved harmony search which is employed as a benchmark.